2008
DOI: 10.1002/jbm.a.32066
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal ligament cellular structures engineered with electrospun poly(DL‐lactide‐co‐glycolide) nanofibrous membrane scaffolds

Abstract: Periodontal tissue engineering is expected to overcome the limitations associated with the existing regenerative techniques for the treatment of periodontal defects involving alveolar bone, cementum, and periodontal ligament. Cell-based tissue engineering approaches involve the utilization of in vitro expanded cells with regenerative capacity and their delivery to the appropriate sites via biomaterial scaffolds. The aim of this study was to establish living periodontal ligament cell-containing structures on el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 26 publications
0
51
0
3
Order By: Relevance
“…124 Others have investigated multicomponent scaffolds, where a gelatinous core is established (by injection) in the mid-substance of a nanofibrous sheet for intervertebral disc applications. 125 Still others have begun to investigate how layers of nanofibers can be seeded with cells, and then stacked to achieve anatomic forms such as periodontal ligament 126 as well as more complicated structures recreating the anatomic form of the IVD and the knee meniscus 127,128 (Fig. 15).…”
Section: Reconstituting Anatomic Formmentioning
confidence: 99%
“…124 Others have investigated multicomponent scaffolds, where a gelatinous core is established (by injection) in the mid-substance of a nanofibrous sheet for intervertebral disc applications. 125 Still others have begun to investigate how layers of nanofibers can be seeded with cells, and then stacked to achieve anatomic forms such as periodontal ligament 126 as well as more complicated structures recreating the anatomic form of the IVD and the knee meniscus 127,128 (Fig. 15).…”
Section: Reconstituting Anatomic Formmentioning
confidence: 99%
“…At 3, 6, 9, and 12 days, it was observed that multilayered hybrid arrangements had developed by deposition of supplementary membrane layers on the existing ones. Thus cell adhesion, viability and osteogenic differentiation was obtained indicating the feasibility of use in periodontal tissue regeneration (Inanç et al, 2009). Kearns and coworkers coated smooth glass and rough titanium substrates with polytetrafluoroethylene (PTFE) nanofibers, cultured human gingival fibroblasts on the substrates and tested the orientation and collagen deposition.…”
Section: Nanofibersmentioning
confidence: 96%
“…Entretanto, essa técnica caminha agora para outro estágio, no qual as membranas serão multifuncionais e não apenas com a função de estabilizar o defeito (INANÇ et al, 2009;PARK et al, 2009).…”
Section: Perspectivasunclassified
“…Essas novas membranas estão sendo chamadas multifuncionais, porque sua estrutura física e constituição química são desenvolvidas para apresentar Ciência Rural, v.41, n.12, dez, 2011. alguma das funções: oclusão da borda superior do defeito para impedir a migração do epitélio juncional na direção apical; maior adesão da gengiva à sua superfície externa, diminuindo assim a possibilidade de ocorrer recessão gengival; propriedades mecânicas adequadas à manutenção do espaço e estabilização da matriz provisória; favorecimento da osteocondução; além de serem reabsorvíveis (CHO et al, 2009;INANÇ et al, 2009;PARK et al, 2009).…”
Section: Perspectivasunclassified
See 1 more Smart Citation